BIOCHRONOLOGY OF THE PLEISTOCENE MAMMAL FAUNA FROM PONTE GALERIA (ROME) AND REMARKS ON THE MIDDLE GALERIAN FAUNAS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
Taking into account the fossil mammal material recently discovered at Cava di Breccia (sands outcropping at Ponte Galeria, Rome), the revised fossils from the area and the updated stratigraphical settings of the Ponte Galeria Formation (Rome), the Authors discuss the biochronology of the Middle Galerian faunal assemblages with a new definition of its Faunal Units.1) The mammal fauna of Isernia in our opinion is strongly conditioned by palaeoenvironmental factors and by human influence. The occurrence at Isernia La Pineta of the rodent Arvicola cantiana, which was widespread in Western Europe from 0.6 MA, does not match with the biochronology of the fauna and with the absolute dating (0.736 MA). A new radiometric dating will be useful to determine the age of the Isernia La Pineta local fauna, which can be considered younger than 0.736 MA on the basis of its faunal assemblage.  2) The age of the faunal assemblage of Ponte Galeria is between 0.8 and 0.75 MA, approximately in correspondence with the Brunhes-Matuyama paleomagnetic reversal event. The first occurrence of Bos galerianus and Megaloceros savini testifies a faunal renewal in comparison with the faunal assemblage of Slivia. The megacerine cervids from Ponte Galeria are more primitive than those from Isernia La Pineta and Venosa-Notarchirico. The Ponte Galeria local fauna has to be considered as a distinct Faunal Unit, younger than Slivia F.U. and older than the Isernia La Pineta fauna. SHORT NOTE